CONSUMERS ATTITUDES TOWARDS MARINATED AND PASTEURISED VEGETABLE - Rodić, Vesna; Vlahović, Branislav; Popović, Zoran (Economics of Agriculture, 2007)
Taking into account the importance that marinated and pasteurized vegetables have in human nutrition, particulary in the seasons when needs for vitamins can not be provided from fresh vegetable, authors in the paper analyze consumers attitudes and motives, which are obtained on the bases of conducted survey. Achieved results can be used by decision makers, both on micro, and macro levels, if their objective is to provide adequate assortment and quality of these products in order to increase their consumption, which is consistent with WHO recommendations.